2015
DOI: 10.1016/j.neuropharm.2015.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic shock-induced cerebral bioenergetic imbalance is corrected by pharmacologic treatment with EF24 in a rat model

Abstract: Maintenance of cerebral viability and function is an important goal of critical care in victims of injury due to ischemia and hypovolemia. As part of the multiple organ dysfunction syndrome, the brain function after trauma is influenced by systemic inflammatory response. We investigated the effect of EF24, an anti-inflammatory bis-chalcone, on cerebral bioenergetics in a rat model of 45% hemorrhagic shock. The rats were treated with EF24 (0.4 mg/kg) or EF24 with an artificial oxygen carrier liposome-encapsulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Several studies have demonstrated a decline in mitochondrial function in HI 41 , 42 . Our recent studies have shown that agents such as resveratrol and SRT1720 that have profound effects on mitochondria can rescue rats following HI in the absence of fluid resuscitation 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a decline in mitochondrial function in HI 41 , 42 . Our recent studies have shown that agents such as resveratrol and SRT1720 that have profound effects on mitochondria can rescue rats following HI in the absence of fluid resuscitation 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Chesnut et al reported that hypovolemia and hypoxia increased TBI-induced morbidity by 150% 6 . HS influences brain injury by causing ischemia, bioenergetic imbalance 21 , and promotion of excitatory signaling in the brain 38,39 . The aggravated TBI+HS tissue injury clinically manifests as increased mortality or severe neurological deficits 6,7,40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Rats in the sham group differed from mTBI rats only in that they did not receive an impact to the brain. Hemorrhagic shock: HS was performed approximately 15-30 min after rats recovered from mTBI surgery anesthesia by withdrawing blood via the arterial catheter as described previously [21][22][23] . Following the constant volume model, varying volumes of blood (0%, 35-40%, 44-46%, and 48-50% of total blood) were withdrawn at a rate of 1.0 ml/min to generate four trauma groups: mTBI alone, mTBI+HS ≤ 40% , mTBI+HS 45% , and mTBI+HS 50%, respectively.…”
Section: Femoral Artery Cannulationmentioning
confidence: 99%
“…This approach suffers from low detection sensitivity and limited tissue penetration, with the major drawback being that NAD + is not detected 14 . The biochemical analysis effectuated with HPLC, capillary electrophoresis or enzymatic cycling assays requires a tissue biopsy and some extraction prior to analysis 15 – 17 . This process might lead to large quantification errors for the highly sensitive redox pairs that have been shown to be rapidly altered after death 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%